Factors associated with adolescent food Security and nutritional status in a selected rural area of the central region of Bangladesh - Akter, Nazifa; Mohammad Kurshed, Ali Abbas (Bioresearch Communications, 2024)
Food insecurity affects physical growth, health of adolescents and nutritional status while food insecurity is common in rural area of Bangladesh. During adolescence, individuals have gone through series of key transitions into adulthood which may be hindered by food insecurity and poor nutritional status. The present study aimed to identify the most relevant factors that may be associated with food security and nutritional status of adolescents. Additionally, this study also tried to explore the association between adolescent food security and their nutritional status. This Cross-sectional study was carried out among 317 unmarried adolescents aged 10 to 19 years in a selected rural area of central region of Bangladesh. Multistage cluster sampling and purposive sampling were followed to select households and enroll adolescents into the study. Other than descriptive statistics, chi-square test was performed to test the difference between groups as well as to evaluate expected associations between different predictors and outcome variables. Additionally, univariate logistic regression was carried out to estimate the effect of predictor variables on the outcome variable. Moreover, multivariate logistic regression analysis was conducted to control the potential confounder effects upon desired outcome variables. It is observed that around 32.5% adolescents were food secure whereas 67.5% adolescents were food insecure. Our study also reveals that two predictor variables such as family income and family size had significant association with food security where odds of becoming food secure were higher among the adolescents from higher income families (AOR=6.1; 95% CI=2.240-16.718) and smaller families (AOR=3.4; 95% CI=1.563, 7.495). Furthermore, prevalence of underweight, normal nutritional status and overweight was 13%, 83% and 4% respectively where adolescent educational qualification and occupation were significantly associated with normal nutritional status. Adolescents with higher educational qualification (AOR=12.3;95% CI=5.270,28.479) and involved in work (AOR=12.3;95% CI=5.270,28.479) were more likely to have normal nutritional status compared to those who were primarily educated and not involved in work. Further study is recommended to replicate the findings and to generate new knowledge about relevant factors associated with adolescent food security and nutritional status. Bioresearch Commu. 10(2): 1573-1582, 2024 (July)